2018
DOI: 10.1021/acs.jcim.8b00535
|View full text |Cite
|
Sign up to set email alerts
|

Structural Approach To Identify a Lead Scaffold That Targets the Translesion Synthesis Polymerase Rev1

Abstract: Translesion synthesis (TLS) is a mechanism of replication past damaged DNA through which multiple forms of human cancer survive and acquire resistance to first-line genotoxic chemotherapies. As such, TLS is emerging as a promising target for the development of a new class of anticancer agents. The C-terminal domain of the DNA polymerase Rev1 (Rev1-CT) mediates assembly of the functional TLS complex through protein–protein interactions (PPIs) with Rev1 interacting regions (RIRs) of several other TLS DNA polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 42 publications
0
42
1
Order By: Relevance
“…[15] In addition, we performed extensive per-residue free energy decomposition profiling from molecular dynamics (MD) simulations of each analogue in complexw ith Rev1-CT to determine which amino acid residues are criticalf or high-affinity binding. [15] In addition, we performed extensive per-residue free energy decomposition profiling from molecular dynamics (MD) simulations of each analogue in complexw ith Rev1-CT to determine which amino acid residues are criticalf or high-affinity binding.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[15] In addition, we performed extensive per-residue free energy decomposition profiling from molecular dynamics (MD) simulations of each analogue in complexw ith Rev1-CT to determine which amino acid residues are criticalf or high-affinity binding. [15] In addition, we performed extensive per-residue free energy decomposition profiling from molecular dynamics (MD) simulations of each analogue in complexw ith Rev1-CT to determine which amino acid residues are criticalf or high-affinity binding.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous MD studies for the core PAP scaffold demonstratedt hat each compound interacts with Leu1159,A la1160, Leu1171, Gln1174, Trp1175, Ile1179,A sp1186, and Glu1189 either by hydrogen bondingo rh ydrophobic interactions ( Figure 1B). [15] Next, we used Glide XP to automatically generate af ourpoint e-pharmacophore hypothesis for each activec ompound complexed with Rev1-CT ( Figure 3). Analysis of the root-mean-square deviation (RMSD)b etween the averaged structure and the isolated ligandsi nc omplex with Rev1-CT demonstrated that both structures correlated well when superimposed (RMSD < 0.1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations